A distinct form of spondyloepimetaphyseal dysplasia with multiple dislocations. Issue 7 (July 1998) - Hall, C M; Elçioglu, N H; Shaw, D G
Abstract : Three unrelated patients with identical radiological features are presented. Hypotonia was noted at birth and one patient was diagnosed as having congenital fibre type disproportion in the neonatal period. Later muscle biopsies, however, were entirely normal. All patients, now in their teens and twenties, are of normal intelligence, show striking epiphyseal and metaphyseal changes of the long bones, and have joint laxity and multiple dislocations of large joints, which are particularly incapacitating at the knees. These three cases represent a sporadic, previously unreported skeletal dysplasia with spondyloepimetaphyseal distribution and multiple large joint dislocations.